“I began to wonder whether I am becoming emotionally numb”. Sociocultural background, hidden curriculum, and moral self-reflection in the development of medical professional identity: A qualitative study - Tereza Pinkasová; Lydie Fialová (Revista Española de Pedagogía, 2025)
The focus of our study is personal, emotional, and moral development of medical students in the context of their medical school experience, and the impact of hidden curriculum on the formation of their professional identity. We conducted interviews with 26 fourth-year students and analysed them by methods of content and discourse analysis. Several factors impacting the adaptation to the medical environment and the adoption of professional identity emerged as significant: their sociocultural background, the institutional culture of medical school, and the practice of moral self-reflection. The adaptation to medical environments and the appropriation of professional roles come more easily to students from medical families, yet present significant challenges to students from non-medical families who are more likely to be impacted by both positive and negative aspects of the hidden curriculum. Students who expressed moral self-reflection were capable of critically assessing the impact of the medical environment on their personal and professional development. We suggest that the provision of safe space for students to reflect on their subjective experiences might be both an educational and therapeutic intervention supporting development of moral and professional integrity, while faculty mentorship might partially compensate for the lack of privilege of medical family background.